ALTERATION OF PHONEMES - Teshaboyeva Nafisa Zubaydulla qizi; Qodirova Iroda Ulugbek qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation: This scientific article seeks to explore sound alternations in phonetics, which involve variations in the pronunciation of sounds within a language. The study investigates various types of sound alternations, the mechanisms that cause them, and the linguistic factors that influence their occurrence. By analyzing existing literature, the article provides a detailed understanding of sound alternations in phonetics, highlighting their importance and implications in the field of linguistics.